Did fair-value accounting contribute to the financial crisis? - Christian Laux; Christian Leuz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
The recent financial crisis has led to a major debate about fair-value accounting. Many critics have argued that fair-value accounting, often also called mark-to-market accounting, has significantly contributed to the financial crisis or, at least, exacerbated its severity. In this paper, we assess these arguments and examine the role of fair-value accounting in the financial crisis using descriptive data and empirical evidence. Based on our analysis, it is unlikely that fair-value accounting added to the severity of the current financial crisis in a major way. While there may have been downward spirals or asset-fire sales in certain markets, we find little evidence that these effects are the result of fair-value accounting. We also find little support for claims that fair-value accounting leads to excessive write-downs of banks' assets. If anything, empirical evidence to date points in the opposite direction, that is, towards overvaluation of bank assets.
urn:nbn:de:hebis:30-72719
Keywords: G14; G15; G30; K22; M41; M42; 330; Mark-to-Market Accounting; Financial Institutions; Liquidity; Financial Crisis; Banks; Financial Regulation; Procyclicality; Contagion; Finanzmarktkrise; Bilanzielle Bewertung; Fair-Value-Bewertung; Bankbilanz; USA